2003
DOI: 10.1051/0004-6361:20030615
|View full text |Cite
|
Sign up to set email alerts
|

An Hαsurvey aiming at the detection of extraplanar diffuse ionized gas in halos of edge-on spiral galaxies

Abstract: Abstract. In a series of two papers we present results of a new Hα imaging survey, aiming at the detection of extraplanar diffuse ionized gas in halos of late-type spiral galaxies. We have investigated a sample of 74 nearby edge-on spirals, covering the northern and southern hemisphere. In 30 galaxies we detected extraplanar diffuse emission at mean distances of |z| ∼ 1−2 kpc. Individual filaments can be traced out to |z| ≤ 6 kpc in a few cases. We find a good correlation between the FIR flux ratio (S 60 /S 10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
155
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(168 citation statements)
references
References 49 publications
10
155
0
Order By: Relevance
“…Under that assumption, the most important properties of a galaxy for determining whether a halo is formed should be (1) the SF energy injection rate (per unit disk area; see e.g. Dahlem et al 1995;Rossa & Dettmar 2003); and (2) the gravitational potential (traced by v 2 rot ). With NGC 891's larger SFR, smaller disk area (at the distances listed in Table 1), and lower rotational velocity, it would seem that it should indeed be more efficient in maintaining a gaseous halo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under that assumption, the most important properties of a galaxy for determining whether a halo is formed should be (1) the SF energy injection rate (per unit disk area; see e.g. Dahlem et al 1995;Rossa & Dettmar 2003); and (2) the gravitational potential (traced by v 2 rot ). With NGC 891's larger SFR, smaller disk area (at the distances listed in Table 1), and lower rotational velocity, it would seem that it should indeed be more efficient in maintaining a gaseous halo.…”
Section: Discussionmentioning
confidence: 99%
“…Star formation-driven disk-halo flows, as described by galactic fountain (e.g., Bregman 1980) or chimney (Norman & Ikeuchi 1989) models, are likely part of the explanation. The morphology of the extraplanar gas seems to be related to the properties of the underlying star forming disk (at least in its ionized phase; e.g., Rand 1996), and whether ionized gas is found in the halo or not seems to depend on the energy density provided by star formation (Rossa & Dettmar 2003).…”
mentioning
confidence: 99%
“…This extraplanar ionized gas is thought to be due to star formation, and it is present in about 40% of 74 edge-on galaxies (Rossa & Dettmar 2003). It can be widely diffuse or take the shape of filaments, plumes, and bubbles (Rand 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of extraplanar H and/or radio emission, as well as extraplanar dust, is known to qualitatively correlate with this parameter (Rand 1996; see also Dettmar 1998;Howk & Savage 1999;Rossa & Dettmar 2000;Dahlem et al 2001). It underestimates the true SF intensity in starburst galaxies, as the SF is often much more concentrated than the old stellar light measured by D 25 .…”
Section: Star Formation Rates and Intensitiesmentioning
confidence: 99%
“…More progress on investigating the disk/halo interface in normal galaxies has been made at other wavelengths, primarily in the optical, where extraplanar H emission (e.g., Dettmar 1992;Rand 1996;Hoopes, Walterbos, & Rand 1999;Collins et al 2000;Rossa & Dettmar 2003;Miller & Veilleux 2003) and dust (Howk & Savage 1999) has been detected in a variety of nearby, normal spiral galaxies. These studies have shown that the presence of such tracers of disk/halo interaction increases with higher levels of star formation (SF) intensity in the underlying disk, but the mechanisms behind these phenomena, and their energetics, are still unclear.…”
Section: Introductionmentioning
confidence: 99%